PSYCHOLOGICAL WELL-BEING SEBAGAI PREDIKTOR THE READINESS FOR SELF-IMPROVEMENT NARAPIDANA - Ardiansyah, Chika Panji; Hamzah, Imaduddin (Journal of Mental Health and Social Rehabilitation, 2025)
Life in an overcrowded correctional facility / detention center causes various problems such as behavioral deviations, prison breaks, riots, fires, drug smuggling, and human rights violations. This surely causes inmates to experience psychological pressure. On the other hand, inmates are required to refine themselves so that they can be socially reintegrated and accepted by society again. Therefore, this study will discuss how the readiness for self-improvement of inmates is influenced by their psychological well-being. This study aims to determine the effect of Psychological Well Being on the inmates' Readiness for Self-Improvement. The method used in this research is a quantitative method. A random sampling technique was used which involved 190 inmates at Surakarta Correctional Facility. The instrument used to measure Psychological Well Being variable was adapted from the scale of Psychological well-being introduced by Ryff, while the scale for Readiness for Self-Improvement variable adapted the Scale of Readiness for Self Improvement (SRSI). The results of the analysis by performing a simple regression test prove that Psychological Well Being is a predictor of The Readiness for Self Improvement with a significance of 21.7%. This reveals that Psychological Well Being contributes to The Readiness for Self-Improvement which causes a need to improve Psychological Well Being to affect The Readiness for Self-Improvement among inmates. This research also aims to contribute to the academic world and add insights in the field of Correctional Sciences regarding inmates in correctional facility. In addition, understanding and knowing the impact of Psychological Well Being on The Readiness for Self-Improvement among inmates could help assist on implementing interventions in correctional facility. Thus the program held for inmates can be more effective and efficient to help them in the reintegration process.